Energetics and Kinetics of Plant Raw Material Dehydration Processes - Burdo O.G.; Terziev S.G.; Burdo A.K.; Sirotyuk I.V.; Pylypenko E.A.; Akimov A.V.; Molchanov M.Yu. (Problems of the Regional Energetics)
The aim of this work is the energy-efficient equipment creation for production of a high-quality dry product from a plant raw material and development of scientific and engineering foundation for the design of such an equipment. The achievement of this aim lies in a deep analysis of ten-dency in the development of a drying theory and technique. The graph is presented, on the basis of which the development of heat and moisture transfer model of A.V. Lykov is given, taking into account the P. A. Rebinder moisture bond forms specificity. The problems of convective drying modern technologies are determined; the reasons of high-energy consumption during their work are substantiated. The electrodynamic dehydrators classification is given, which con-sideres the combined simple modes (drying) and hybrid dehydration modes. On the basis of the first law of thermodynamics, the possibility of a significant decrease in energy consumption is shown by the organization of a “vapordynamic” effect. The most significant result of the work is the construction of the electrodynamic apparatus module for dehydration of food and medici-nal plant raw material. By the combination of electromagnetic field with the filtration process the specific energy consumptions were 1.9 MJ per 1 kg of the removed moisture, at the hybrid pro-cesses — juice yield exceeded vapor yield by 3.5 times. The significance of the work consists in the fact that the scientific conception of the authors on the possibilities of the significant de-crease in energy consumption during the raw material dehydration at the innovative electrody-namic type apparatuses was practically proven.